A Rationally Designed Bovine IgA Fc Scaffold Enhances in planta Accumulation of a VHH-Fc Fusion Without Compromising Binding to Enterohemorrhagic E. coli - Chin-Fatt, Adam; Saberianfar, Reza; Menassa, Rima (Frontiers in Plant Science, 2021)
We previously isolated a single domain antibody (VHH) that binds Enterohemorrhagic Escherichia coli (EHEC) with the end-goal being the enteromucosal passive immunization of cattle herds. To improve the yield of a chimeric fusion of the VHH with an IgA Fc, we employed two rational design strategies, supercharging and introducing de novo disulfide bonds, on the bovine IgA Fc component of the chimera. After mutagenizing the Fc, we screened for accumulation levels after transient transformation in Nicotiana benthamiana leaves. We identified and characterized five supercharging and one disulfide mutant that improve accumulation in comparison to the native Fc. Combining all these mutations is associated with a 32-fold increase of accumulation for the Fc alone, from 23.9 mg/kg fresh weight (FW) to 599.5 mg/kg FW, as well as a twenty-fold increase when fused to a VHH that binds EHEC, from 12.5 mg/kg FW tissue to 236.2 mg/kg FW. Co-expression of native or mutated VHH-Fc with bovine joining chain (JC) and bovine secretory component (SC) followed by co-immunoprecipitation suggests that the stabilizing mutations do not interfere with the capacity of VHH-Fc to assemble with JC and FC into a secretory IgA. Both the native and the mutated VHH-Fc similarly neutralized the ability of four of the seven most prevalent EHEC strains (O157:H7, O26:H11, O111:Hnm, O145:Hnm, O45:H2, O121:H19 and O103:H2), to adhere to HEp-2 cells as visualized by immunofluorescence microscopy and quantified by fluorometry. These results collectively suggest that supercharging and disulfide bond tethering on a Fc chain can effectively improve accumulation of a VHH-Fc fusion without impacting VHH functionality.